The distribution of nutrients and chlorophyll-a in the temperate coast of China: implications for marine ecological risks in the context of global warming - Bai, Dapeng; Chu, Hongxian; Feng, Yongcai; Wang, Lixin; Yin, Meiling (Frontiers in Marine Science, 2025)
IntroductionNutrients directly regulate the level of primary productivity, which is crucial for the stability of marine ecosystems. However, under the context of human activities leading to global warming, factors influencing alterations in coastal nutrient dynamics remain a mystery.MethodsA study was conducted to investigate the spatial distribution characteristics of nutrients and chlorophyll-a at 55 stations in the Bohai Bay region during the autumn of 2021.ResultsThe dominant factor influencing coastal zone ecology in the surveyed area was identified as temperature. Multiple factors (e.g., riverine input, sediment release, atmospheric deposition, and hydrodynamics) collectively impacted nutrient dynamics. The temperature along the north-south transect was consistent, with a distinct demarcation at 118.68°E (19°C), where the temperature gradient exhibited a pronounced east-high, west-low pattern. The temperature difference between the surface and bottom waters was minimal. In the high-temperature eastern region, the redox potential was high (above 100 mV), and very few locations had low dissolved oxygen levels, indicating active aerobic microbial activity. This led to the decomposition of substantial organic matter, resulting in elevated ammonia-nitrogen concentrations, and low pH levels. The presence of ammonia-nitrogen promoted the growth and reproduction of planktonic organisms.DiscussionTherefore, we are concerned that global climate warming may trigger changes, and even worsen, marine ecological environments in temperate coastal regions, necessitating heightened attention from researchers.